Terra dos mortos: o espaço narrativo nos filmes de zumbis - Gomes, Paula (Universidade Federal de São Carlos, 2014)
This study aims to analyze the genre of zombie movies establishing a dialogue between their narrative spaces, the historical contexts in which they are situated, and their connections to other works in different media, in an intermedial perspective. Therefore, this research sought to study three narrative spaces that were widely used in the films of the genre: the Caribbean space, used in 1930-1940 American films of the Haitian zombie; internal and external areas of the United States, seen in flesh eaters zombie films created by George Romero in the second half of the 20th century; and major world capitals destroyed, present in many contemporary zombie films from various countries. In this context, this study main objective is to perform a spatial analysis of zombie films, that explores the possible connections and interrelations between the colonial metropolis/colony, inside/outside, and national/global spatial dichotomies, with the historical and social contexts in which these works are contained.
Keywords: Gêneros cinematográficos; Filmes de horror; Filmes de zumbis; Narração; Audiovisual genres; Horror; Zombie movies; Narrative space; LINGUISTICA, LETRAS E ARTES::ARTES::CINEMA